Apuração da margem de contribuição na microcervejaria Gole Mágico: um estudo de caso - Araujo, Guilherme Albertão de (Universidade do Vale do Rio dos Sinos, 2015)
Competing in the business environment in which companies operate currently requires multiple skills that need to be worked together throughout the organization. There are numerous skills that managers and all other company employees need to adapt to the constant changes that occur in the market. The knowledge of how to behave in the production costs are among the most important needs within organizations. This is due to the fact that, acting in an increasingly competitive market, companies are required to work with increasingly lean to stay healthy and perpetuate the market costs. Product prices are given by the market and companies find themselves forced to work daily to reduce their production costs. This paper aims to contribute to the knowledge of the production costs and the production process of Microcervejaria Gole Mágico and thus improve their performance and participation in the craft beer market. By identifying the production process and the identification of variable costs and fixed unit looking to determine the unit contribution margin of microbrews company. The identification of the unit contribution margin contributes to the knowledge of production and the change in costs in different production levels. The Microcervejaria Gole Mágico is not exception to the rule and is embedded in an increasingly competitive market. To do this, you must have inside information that contribute to face the uncertainties that the market requires the company and that often can not be predicted in advance. The determination of the contribution margins of the beers produced by Microcervejaria Gole Mágico is of fundamental importance for the growth and support of the company because by knowing the unit contribution margins the company is able to prioritize production and sale or opt for quit some kind of craft beer is found forward production unfeasibility the unit contribution margins presented.
Keywords: Mercado; Custos de Produção; Microcervejaria Gole Mágico; Processos; Margem de contribuição unitária; Marketing; Production Costs; Microcervejaria Gole Mágico; Processes; Unit contribution margin